Anodic Stripping Voltammetry with a Dynamic Flow-through Sequential Extraction Method for Fractionation Study of Cadmium and Lead in Soil - Autchara Paukpol (2020)
© 2020, © 2020 Taylor & Francis. A powerful anodic stripping voltammetry (ASV) was proposed using a bismuth film coated on screen-printed carbon electrode (Bi-SPCE) in conjunction with the Tessier’s sequential extraction procedure for determination of various forms of cadmium and lead in soil. A dynamic flow-through stirred extraction system was employed to simulate the natural percolation of liquid through the solid soil that causes leaching of trace metals. The voltammetric peak currents, linear ranges, and detection limits of the metal ions depend on the type and condition of the extractants. The effect of interferences can be eliminated by acid digestion of the extract, addition of 0.3 mM ferricyanide, and adjustment of the pH. As validated with a certified reference material of sandy loam soil (CRM033), this low-cost ASV with Bi-SPCE system could be used successfully for the analysis of metals in the leachate. The proposed method provided high accuracy and precision with high sensitivity. Analysis time was reduced by one-fourth that of the batch-wise method. The performance of the proposed method was also demonstrated for the fractionation study of a soil sample from a mining area in northern Thailand.